2002
DOI: 10.1128/cdli.9.6.1145-1152.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the Pathogenesis of and Protection against Malaria

Abstract: Malaria is caused by the protozoan Plasmodium, transmitted to humans by Anopheles mosquitoes. The most dangerous of the plasmodia infecting humans is Plasmodium falciparum. Most of the clinical signs of this disease are caused by the parasite at stages in which it multiplies asexually in red blood cells. P. falciparum infection is most severe in children. However, only a small proportion of infected children develop severe complications; in nonimmune individuals these can cause severe and life-threatening dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
111
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 102 publications
6
111
1
4
Order By: Relevance
“…Several parasite virulence factors that interact with Toll-like receptors, including hemozoin with TLR9 (6) and GPIs with TLR2 and TLR4 (23,29), that induce signal transduction pathways through the transcription factor NF-B, which in turn propagates signals to the nucleus to regulate the expression of proinflammatory cytokines such as TNF-␣, IL-1␤, and IL-6 and chemokines such as macrophage inflammatory protein 1␣ and IL-8 (22,46), have recently been demonstrated. Significantly, expression levels of these proinflammatory cytokines correlate directly with the severity of disease (1,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parasite virulence factors that interact with Toll-like receptors, including hemozoin with TLR9 (6) and GPIs with TLR2 and TLR4 (23,29), that induce signal transduction pathways through the transcription factor NF-B, which in turn propagates signals to the nucleus to regulate the expression of proinflammatory cytokines such as TNF-␣, IL-1␤, and IL-6 and chemokines such as macrophage inflammatory protein 1␣ and IL-8 (22,46), have recently been demonstrated. Significantly, expression levels of these proinflammatory cytokines correlate directly with the severity of disease (1,18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously established that the level of proinflammatory cytokine secretion in malaria infection correlates directly with the severity of disease (1,2,18). In particular, TNF-␣ has numerous biological effects on host cells including the upregulation of adhesion molecules such as intracellular adhesion molecule 1 (CD54) on the surface of postcapillary endothelium (4,10,43) to which malaria-infected erythrocytes sequester (31).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-10 has been shown to reduce the inflammatory immune reaction mediated by pro-inflammatory cytokines such as IFN-γ and TNF-α, but at the expense of host ability to control the infecting parasite. [33][34][35][36] Mouse studies have consistently shown IL-10 to be an important cytokine in decreasing inflammation and protecting the host in murine malaria models. [37][38][39] In human malaria, several studies have demonstrated association of low IL-10 levels with more severe disease such as cerebral malaria and severe anemia.…”
Section: Discussionmentioning
confidence: 99%
“…12 Liver is an alternative organ besides the spleen as a place for eliminating the parasitized red cells. 16 We found splenomegaly in 37 (35.6 %) patients. This result was smaller than that of other study which found splenomegaly in 45% to 75% of patients.…”
Section: Discussionmentioning
confidence: 95%